Migration, Identity, and Threatened Mental Health: Examples from Contemporary Fiction. (October 2019) - Wigand, Moritz E.; Wiegand, Hauke F.; Altintas, Ertan; Jäger, Markus; Becker, Thomas
In 2015, the world saw 244 million international migrants. Migration has been shown to be both a protective and a risk factor for mental health, depending on circumstances. Furthermore, culture has an impact on perceptions and constructions of mental illness and identity, both of which can be challenged through migration. Using a qualitative research approach, we analysed five internationally acclaimed and influential novels and one theatre play that focus on aspects of identity, migration, and threatened mental health. As a mirror of society, fiction can help to understand perceptions of identity and mental suffering on an intrapsychic and societal level, while at the same time society itself can be influenced by works of fiction. Fiction is also increasingly used for didactic purposes in medical education. We found that the works of fiction discussed embrace a multifaceted biopsychosocial concept of mental illness. Constructs such as unstable premigration identity, visible minority status (in the host country) and identity confusion in second-generation migrants are conceptualised as risk factors for mental illness. Factors portrayed as protective comprised a stable premigration identity, being safe with a family member or good friend, (romantic) love, therapeutic writing, art, and the concept of time having an element of simultaneousness. This literature challenges the idiocentric model of identity. Analysing fictional texts on migration experiences can be a promising hypothesis-generating approach for further research.